The Intimacy of Internationalism in the Poetry of Joachim Sartorius - Neil H. Donahue (Studies in 20th & 21st Century Literature, 1997)
This article considers Joachim Sartorius in his various cultural and literary activities as diplomat, administrator, editor, translator, and poet as a possible model for the German intellectual after reunification, and links those activities through the concept of "internationalism," which has shifted in meaning from programmatic politics to an understanding of cultural difference and mediation with an Other, whether as public and private spheres, Self and Other, or Subject and Object. For Sartorius, however, poetry defines most closely or most intimately that notion of mediation, and thus requires 'close' reading. That notion distances him from the 'impersonal' Modernist poetics of Bertolt Brecht and Gottfried Benn, and links him internationally to W. C. Williams and Pierre Jean Jouve. By examining that connection, this essay defines the international and philosophical base for Sartorius's poetics of intimacy.
Keywords: Joachim Sartorius; cultural; literary activities; diplomat; administrator; editor; translator; poet; German intellectual; reunification; internationalism; cultural difference; mediation; other; public spheres; private spheres; Self and Other; Subject; Object; poetry; impersonal; modernist; Bertolt Brecht; Gottfried Benn; W. C. Williams; Pierre Jean Jouve; poetics of intimacy; intimacy